The development competencies of future informatics teachers in the learning process linear algebra (Pedagogy of Higher and Secondary Education, 2014)
Armash T. S. The development competencies of future informatics teachers in the learning process linear algebra.Considers the main competence of future teachers of informatics and allocated those that are formed in the study of linear algebra, the article allocated production functions and abilities of the student-computer science generated in the study of linear algebra.
Keywords: teachers of computer science; linear algebra; professional training; competence